Laminate and tube container body

The use of a polyethylene-based laminate for tube containers addresses the recyclability issue by allowing all components to be reused, enhancing the environmental sustainability of tube containers.

JP7608045B2Active Publication Date: 2025-01-06DAI NIPPON PRINTING CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2019180907
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-25
Filing Date
2019-09-30
Publication Date
2025-01-06
Estimated Expiration
2039-09-30

AI Technical Summary

Technical Problem

Conventional tube container bodies are difficult to recycle due to their laminates composed of different materials, which cannot be easily separated.

Method used

A laminate structure for tube containers made entirely of polyethylene, including a surface resin layer, base material, and heat seal layer, with optional gas barrier and adhesive layers, where all layers are made of the same polyethylene material, allowing for high recyclability.

Benefits of technology

Enables the production of tube containers with high recyclability by ensuring all components can be reused, reducing environmental impact and facilitating efficient recycling processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608045000009
    Figure 0007608045000009
  • Figure 0007608045000010
    Figure 0007608045000010
  • Figure 0007608045000011
    Figure 0007608045000011
Patent Text Reader

Abstract

To provide a laminate capable of preparing a tube container body having high recyclability.SOLUTION: A laminate 10 includes a surface resin layer 11, a base material 12, a gas barrier layer 13 and a heat seal layer 14. The surface resin layer, the base material and the heat seal layer are composed of the same material. The base material includes a vapor-deposited film 15 on at least one surface thereof. The surface resin layer has heat sealability. The same material is polyethylene. A melt-extruded polyethylene layer or adhesive layer is provided between at least one or more between the surface resin layer and the base material, between the base material and the gas barrier layer, and the gas barrier layer and the heat seal layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate and a tube container body including the laminate.

[0002] Tube containers, which include a tube container body and a cap, are known as packaging containers that are filled with a semi-liquid paste such as toothpaste or face wash cream and then squeezed out for use. The tube container body generally has a structure that includes a cylindrical body portion that is closed at one end and open at the other end, and a head portion that has a spout that is connected to the other open end of the body portion. The body portion is filled with the contents, and then the one end is closed to produce a tube container containing the contents. As a laminate constituting the barrel of a tube container body, a laminate of a polyethylene film, a polyester film, a gas barrier layer, an aluminum foil, etc. is widely used (for example, Patent Documents 1 and 2, etc.).

[0003] In recent years, with the growing demand for the creation of a recycling-oriented society, there is a demand for packaging containers with high recyclability. However, as described above, the body portion of a conventional tube container body is made up of a laminate having layers of multiple different materials, and since it is difficult to separate the layers of different materials, they are not currently recycled. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2006-282184 A [Patent Document 2] JP 2014-231372 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made in view of the above problems, and an object of the present invention is to provide a laminate from which a tube container body having high recyclability can be produced. Another problem to be solved by the present invention is to provide a tube container body including the laminate. [Means for solving the problem]

[0006] The laminate of the present invention comprises a surface resin layer, a substrate, a gas barrier layer, and a heat seal layer, The surface resin layer, the base material and the heat seal layer are made of the same material, The substrate has a vapor-deposited film on at least one surface thereof, The surface resin layer has a heat sealability, The uniform material is characterized by being polyethylene.

[0007] In one embodiment, the laminate of the present invention comprises a melt-extruded polyethylene layer or an adhesive layer at least one of between the surface resin layer and the substrate, between the substrate and the gas barrier layer, and between the gas barrier layer and the heat seal layer.

[0008] In one embodiment, the polyethylene constituting the surface resin layer and the heat seal layer is a low-density polyethylene and / or a linear low-density polyethylene.

[0009] In one embodiment, the vapor-deposited film is a vapor-deposited metal film.

[0010] In one embodiment, the gas barrier layer comprises a first polyethylene resin layer, a first adhesive layer, a layer containing a gas barrier resin, a second adhesive layer, and a second polyethylene resin layer.

[0011] In one embodiment, the layer containing the gas barrier resin has a thickness of 5 μm or more and 30 μm or less.

[0012] In one embodiment, the thickness of the surface resin layer and the heat seal layer is 50 μm or more and 150 μm or less.

[0013] In one embodiment, the thickness of the substrate is 10 μm or more and 50 μm or less.

[0014] In one embodiment, the thickness of the deposited film is 1 nm or more and 150 nm or less.

[0015] In one embodiment, the polyethylene content in the entire laminate is 90% by mass or more.

[0016] In one embodiment, the laminate of the present invention is used in a tube container application.

[0017] The tube container of the present invention comprises a head portion and a body portion, The head portion has a shoulder portion connected to one end of the body portion and a sampling port portion connected to the shoulder portion, The body portion is characterized by being formed from the above laminate.

[0018] In one embodiment, the head portion is made of a resin composition containing polyethylene.

[0019] In one embodiment, the tube container further includes a cap made of a resin composition containing polyethylene. Effect of the Invention

[0020] According to the present invention, it is possible to provide a laminate from which a tube container having high recyclability can be produced. Also, according to the present invention, it is possible to provide a tube container body having high recyclability, which includes the laminate. [Brief description of the drawings]

[0021] [Figure 1] 1 is a schematic cross-sectional view showing one embodiment of a laminate of the present invention. [Diagram 2]FIG. 1 is a perspective view showing one embodiment of a tube container comprising a tube container body including a laminate of the present invention and a cap. [Diagram 3] 3 is a cross-sectional view taken along line AA in FIG. 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] (Laminate) As shown in FIG. 1, the laminate 10 of the present invention comprises a surface resin layer 11, a substrate 12, a gas barrier layer 13, and a heat seal layer 14, and is characterized in that the substrate 12 has a vapor deposition film 15 on at least one surface thereof. The vapor-deposited film 15 can improve the design of a tube container produced using the laminate of the present invention, and is therefore preferably provided on the surface of the substrate on the side of the front resin layer. Since the surface resin layer 11, the base material 12 and the heat seal layer 14 of the laminate 10 of the present invention are made of the same material, namely polyethylene, the laminate 10 of the present invention has high recyclability, and the tube container body comprising this laminate also has high recyclability.

[0023] In one embodiment, the laminate 10 of the present invention includes a melt-extruded polyethylene layer 16 or an adhesive layer 17 between the surface resin layer 11 and the substrate 12, between the substrate 12 and the gas barrier layer 13, and between the gas barrier layer 13 and the heat seal layer 14, as shown in FIG. 1.

[0024] In one embodiment, the substrate 12 includes a barrier coat layer (not shown) below or above the deposited film 15.

[0025] The content of polyethylene in the entire laminate of the present invention is preferably 90% by mass or more, and more preferably 95% by mass or more, which can improve the recyclability of the laminate of the present invention and the tube container including the laminate.

[0026] (Surface resin layer and heat seal layer) The surface resin layer and the heat seal layer constituting the laminate of the present invention are made of polyethylene and both have heat sealability. As the polyethylene, high density polyethylene, medium density polyethylene, low density polyethylene, linear low density polyethylene and very low density polyethylene can be used. Among these, from the viewpoint of heat sealability, low density polyethylene and / or linear low density polyethylene are preferred.

[0027] In the present invention, the high density polyethylene has a density of 0.945 g / cm 3 The polyethylene having a density of 0.925 g / cm3 or more can be used. 3 More than 0.945g / cm 3 Polyethylene having a density of less than 0.900 g / cm3 can be used. 3 More than 0.925g / cm 3 For linear low density polyethylene, a polyethylene having a density of 0.900 g / cm3 or less can be used. 3 More than 0.925g / cm 3 For ultra-low density polyethylene, a polyethylene having a density of 0.900 g / cm3 can be used. 3 Less than 100 mm of polyethylene can be used.

[0028] In the present invention, the polyethylene includes copolymers of ethylene and other monomers. Examples of ethylene copolymers include copolymers of ethylene and α-olefins having 3 to 20 carbon atoms, and examples of α-olefins having 3 to 20 carbon atoms include propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 3-methyl-1-butene, 4-methyl-1-pentene, and 6-methyl-1-heptene. In addition, the polyethylene may be a copolymer with vinyl acetate or an acrylic acid ester, etc., as long as it does not impair the object of the present invention.

[0029] The surface resin layer and the heat seal layer can contain biomass-derived polyethylene obtained by polymerizing a monomer containing biomass-derived ethylene, and since such biomass-derived polyethylene is a carbon-neutral material, the environmental load in producing the laminate of the present invention can be reduced. Since biomass-derived ethylene is used as the raw material monomer, the polymerized polyethylene is derived from biomass. Note that the raw material monomer of the polyethylene does not have to contain 100% by mass of biomass-derived ethylene.

[0030] The monomers that are the raw material for the biomass-derived polyethylene may further contain ethylene and / or α-olefins derived from fossil fuels, or may further contain α-olefins derived from biomass.

[0031] The concentration of ethylene derived from biomass in the polyethylene contained in the surface resin layer and the heat seal layer (hereinafter sometimes referred to as "biomass degree") is preferably 10% or more. "Biomass content" is a value measured by radiocarbon (C14) measurement to determine the amount of carbon derived from biomass. Carbon dioxide in the atmosphere contains a certain percentage of C14 (105.5 pMC), so it is known that the C14 content in plants that grow by absorbing carbon dioxide from the atmosphere, such as corn, is also about 105.5 pMC. It is also known that fossil fuels contain very little C14. Therefore, the proportion of carbon derived from biomass can be calculated by measuring the proportion of C14 in the total carbon atoms in the polyethylene. C14 The content of carbon derived from biomass, P bio It can be calculated as follows: P bio (%)=P C14 / 105.5×100

[0032] In the present invention, theoretically, if all ethylene derived from biomass is used as a raw material for polyethylene, the concentration of biomass-derived ethylene is 100%, and the biomass content of the biomass-derived polyethylene is 100%. In addition, the concentration of biomass-derived ethylene in fossil fuel-derived polyethylene produced only from fossil fuel-derived raw materials is 0%, meaning that the biomass content of fossil fuel-derived polyethylene is 0%.

[0033] Biomass-derived ethylene can be produced using biomass-derived ethanol as a raw material. In particular, it is preferable to use biomass-derived fermented ethanol obtained from a plant raw material. The plant raw material is not particularly limited, and any conventionally known plant can be used. Examples of the plant raw material include corn, sugarcane, beet, and manioc.

[0034] In the present invention, the fermented ethanol derived from biomass refers to ethanol produced by contacting a culture solution containing a carbon source obtained from a plant raw material with an ethanol-producing microorganism or a product derived from its crushed material, and then purifying the ethanol. Conventionally known methods such as distillation, membrane separation, and extraction can be applied to purify ethanol from the culture solution. For example, there is a method of adding benzene, cyclohexane, etc., and removing water by azeotropy or membrane separation.

[0035] A catalyst is usually used when obtaining ethylene by the dehydration reaction of ethanol, but the catalyst is not particularly limited and any conventionally known catalyst can be used. From the viewpoint of the process, a fixed bed flow reaction is advantageous because it is easy to separate the catalyst from the product, and for example, γ-alumina is preferable.

[0036] This dehydration reaction is an endothermic reaction, and is usually carried out under heating conditions. As long as the reaction proceeds at a commercially useful reaction rate, the heating temperature is not limited, but is preferably 100° C. or higher, more preferably 250° C. or higher, and even more preferably 300° C. or higher. There is no particular upper limit, but from the viewpoint of energy balance and equipment, it is preferably 500° C. or lower, more preferably 400° C. or lower.

[0037] The reaction pressure is not particularly limited, but is preferably equal to or higher than atmospheric pressure in order to facilitate the subsequent gas-liquid separation. From an industrial perspective, a fixed bed flow reaction is preferred because it is easy to separate the catalyst, but a liquid phase suspension bed, a fluidized bed, or the like may also be used.

[0038] In the dehydration reaction of ethanol, the yield of the reaction depends on the amount of water contained in the ethanol supplied as a raw material. In general, when performing a dehydration reaction, it is preferable to have no water, considering the efficiency of removing water. However, in the case of the dehydration reaction of ethanol using a solid catalyst, it has been found that the amount of other olefins, especially butene, produced tends to increase if water is not present. It is presumed that this is because ethylene dimerization after dehydration cannot be suppressed if a small amount of water is not present. The lower limit of the allowable water content is 0.1% or more, preferably 0.5% or more. There is no particular limit to the upper limit, but from the viewpoint of material balance and heat balance, it is preferably 50% by weight or less, more preferably 30% or less, and even more preferably 20% or less.

[0039] By carrying out the dehydration reaction of ethanol in this manner, a mixture of ethylene, water and a small amount of unreacted ethanol is obtained, but since ethylene is in a gaseous state at room temperature under about 5 MPa or less, water and ethanol can be removed from this mixture by gas-liquid separation to obtain ethylene. This method may be performed by any known method.

[0040] The ethylene obtained by the gas-liquid separation is further distilled. The distillation method, operation temperature, residence time, etc. are not particularly limited, except that the operation pressure at this time is normal pressure or higher.

[0041] When the raw material is biomass-derived ethanol, the obtained ethylene contains extremely small amounts of carbonyl compounds such as ketones, aldehydes, and esters, which are impurities mixed in during the ethanol fermentation process, as well as carbon dioxide, which is a decomposition product thereof, and nitrogen-containing compounds such as amines and amino acids, which are enzyme decomposition products and impurities, as well as ammonia, which is a decomposition product thereof. Depending on the use of ethylene, these extremely small amounts of impurities may be problematic, so they may be removed by purification. The purification method is not particularly limited, and can be performed by a conventionally known method. An example of a suitable purification operation is an adsorption purification method. The adsorbent used is not particularly limited, and a conventionally known adsorbent can be used. For example, a material with a high surface area is preferable, and the type of adsorbent is selected according to the type and amount of impurities in the ethylene obtained by the dehydration reaction of biomass-derived ethanol.

[0042] In addition, a caustic water treatment may be used in combination as a method for purifying impurities in ethylene. When caustic water treatment is used, it is preferable to carry out the treatment before adsorption purification. In that case, it is necessary to carry out a water removal treatment after the caustic treatment and before the adsorption purification.

[0043] The surface resin layer and the heat seal layer may also contain polyethylene recycled by mechanical recycling. Here, mechanical recycling generally refers to a method in which recovered polyethylene films are crushed and washed with an alkali to remove dirt and foreign matter from the film surface, and then dried at high temperature and reduced pressure for a certain period of time to diffuse and decontaminate the contaminants remaining inside the film, thereby removing dirt from the polyethylene film and returning it to polyethylene.

[0044] The surface resin layer and the heat seal layer may contain additives within the range that does not impair the characteristics of the present invention. Examples of such additives include crosslinking agents, antioxidants, antiblocking agents, slip agents, UV absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, and modifying resins.

[0045] In one embodiment, the surface resin layer and the heat seal layer are made of a film made of polyethylene, and the film may be a stretched film or an unstretched film. From the viewpoint of heat sealability, the film is preferably an unstretched film.

[0046] The surface resin layer and the heat seal layer may be subjected to a surface treatment, which can improve the adhesion between the adjacent layers. The method of surface treatment is not particularly limited, and examples thereof include physical treatments such as corona discharge treatment, ozone treatment, low-temperature plasma treatment using oxygen gas and / or nitrogen gas, and glow discharge treatment, as well as chemical treatments such as oxidation treatment using chemicals. Furthermore, an anchor coat layer may be formed on the surface of the surface resin layer and the heat seal layer by using a conventionally known anchor coat agent.

[0047] The thickness of the surface resin layer and the heat seal layer is preferably 30 μm or more and 150 μm or less, and more preferably 50 μm or more and 120 μm or less. The thickness of the surface resin layer and the thickness of the heat seal layer may be the same or different. By making the thickness of the surface resin layer and the heat seal layer 30 μm or more, the heat sealability can be further improved. Furthermore, by setting the thickness of the surface resin layer and the heat seal layer to 150 μm or less, the processability of the laminate including the substrate can be improved.

[0048] In one embodiment, the surface resin layer and the heat seal layer can be produced by forming a resin composition containing at least polyethylene into a film using a T-die method, an inflation method, or the like. The surface resin layer and the substrate can be laminated via a melt-extruded polyethylene layer or an adhesive layer, which will be described later.

[0049] (base material) The substrate constituting the laminate of the present invention is made of polyethylene, and as the polyethylene, high density polyethylene, medium density polyethylene, low density polyethylene, linear low density polyethylene and very low density polyethylene can be used. Among these, high density polyethylene and medium density polyethylene are preferred from the viewpoint of the strength and heat resistance of the substrate, and medium density polyethylene is more preferred from the viewpoint of the stretchability.

[0050] The substrate may contain biomass-derived polyethylene, and the concentration of biomass-derived ethylene in the polyethylene contained in the substrate (hereinafter sometimes referred to as "biomass degree") is preferably 10% or more.

[0051] The substrate can also include recycled polyethylene through mechanical recycling.

[0052] The base material may contain the above-mentioned additives to the extent that the characteristics of the present invention are not impaired.

[0053] In one embodiment, the substrate has a multi-layer structure. For example, the laminate may be configured to include a layer made of low density polyethylene, a layer made of high density polyethylene, and a layer made of low density polyethylene.

[0054] In one embodiment, the substrate is made of a film made of polyethylene, and the film may be a stretched film or an unstretched film.

[0055] The substrate may be subjected to a surface treatment, which can improve the adhesion between adjacent layers. The method of surface treatment is not particularly limited, and examples thereof include physical treatments such as corona discharge treatment, ozone treatment, low-temperature plasma treatment using oxygen gas and / or nitrogen gas, and glow discharge treatment, as well as chemical treatments such as oxidation treatment using chemicals. Furthermore, an anchor coat layer may be formed on the surface of the substrate using a conventionally known anchor coat agent.

[0056] The substrate may have a printed layer on its surface. The image formed on the printed layer is not particularly limited, and may be a character, a pattern, a symbol, or a combination thereof. From the viewpoint of environmental impact, the formation of a printed layer on a substrate is preferably carried out using an ink derived from biomass. The method for forming the printed layer is not particularly limited, and examples of the method include conventionally known printing methods such as gravure printing, offset printing, flexographic printing, etc. Among these, flexographic printing is preferred from the viewpoint of environmental load.

[0057] The thickness of the substrate is preferably 10 μm or more and 50 μm or less, and more preferably 20 μm or more and 40 μm or less. By making the thickness of the substrate 10 μm or more, the strength and heat resistance can be further improved. Furthermore, by setting the thickness of the substrate to 50 μm or less, the processability of the laminate including the substrate can be improved.

[0058] In one embodiment, the substrate can be produced by forming a resin composition containing at least polyethylene into a film using a T-die method, an inflation method, or the like.

[0059] (evaporated film) The substrate has a vapor-deposited film on at least one surface thereof, which can improve the gas barrier properties of the laminate, specifically the oxygen barrier properties and water vapor barrier properties. The vapor-deposited film is preferably provided on the gas barrier layer side surface of the substrate, since it can improve the design of a tubular container produced using the laminate of the present invention.

[0060] The vapor-deposited film may be composed of a metal or an inorganic oxide, but a vapor-deposited film composed of a metal (hereinafter referred to as a metal vapor-deposited film) is preferred because it can impart a glossy appearance to tube containers and the like produced using the laminate of the present invention and improve their design. Examples of metals that can be used to form the metal vapor deposition film include aluminum, chromium, tin, nickel, copper, silver, gold, and platinum. Examples of the metal oxide include aluminum oxide, silicon oxide, magnesium oxide, calcium oxide, zirconium oxide, titanium oxide, boron oxide, hafnium oxide, and barium oxide.

[0061] The surface of the deposited film is preferably subjected to the above-mentioned surface treatment, which can improve adhesion to adjacent layers.

[0062] The thickness of the evaporated film is preferably 1 nm or more and 150 nm or less, and more preferably 5 nm or more and 60 nm or less. By making the thickness of the vapor-deposited film 1 nm or more, the oxygen barrier property and water vapor barrier property of the laminate can be further improved, and when it is a metal vapor-deposited film, a higher gloss can be imparted. By setting the thickness of the deposited film to 150 nm or less, it is possible to prevent the occurrence of cracks in the deposited film and also to maintain the recyclability of the laminate.

[0063] The deposition film on the substrate can be formed by a conventional method, for example, physical vapor deposition methods (PVD methods) such as vacuum deposition, sputtering, and ion plating, and chemical vapor deposition methods (CVD methods) such as plasma chemical vapor deposition, thermal chemical vapor deposition, and photochemical vapor deposition.

[0064] Also, for example, a composite film consisting of two or more layers of vapor-deposited films of different inorganic oxides can be formed and used by combining both physical vapor deposition and chemical vapor deposition. The degree of vacuum in the vapor deposition chamber is 10 -2 ~10 -8 After oxygen is introduced, the pressure is preferably about 10 -1 ~10 -6 The pressure is preferably about mbar. The amount of oxygen introduced varies depending on the size of the deposition machine. For the oxygen to be introduced, an inert gas such as argon gas, helium gas, or nitrogen gas may be used as a carrier gas to the extent that no problems occur. The film transport speed can be about 10 to 800 m / min.

[0065] (Barrier coat layer) In one embodiment, the substrate is provided with a barrier coat layer below or above the deposition layer, which can improve the oxygen barrier property and water vapor barrier property of the laminate. When the substrate has a vapor-deposited film, the barrier coat layer may be provided on or under the vapor-deposited film.

[0066] In one embodiment, the barrier coat layer contains a gas barrier resin such as an ethylene-vinyl alcohol copolymer (EVOH), polyvinyl alcohol, polyacrylonitrile, polyamide such as nylon 6, nylon 6,6, and polymetaxylylene adipamide (MXD6), polyester, polyurethane, and (meth)acrylic resin. Among these, polyvinyl alcohol is preferred from the viewpoint of oxygen barrier property and water vapor barrier property. Furthermore, when the vapor-deposited film is made of an inorganic oxide, the occurrence of cracks in the vapor-deposited film can be effectively prevented by including polyvinyl alcohol in the barrier coat layer.

[0067] The content of the gas barrier resin in the barrier coat layer is preferably 50% by mass or more and 95% by mass or less, and more preferably 75% by mass or more and 90% by mass or less. By making the content of the gas barrier resin in the barrier coat layer 50% by mass or more, the oxygen barrier property and water vapor barrier property of the substrate can be further improved.

[0068] The barrier coat layer may contain the above-mentioned additives to the extent that the characteristics of the present invention are not impaired.

[0069] The thickness of the barrier coat layer is preferably 0.01 μm or more and 10 μm or less, and more preferably 0.1 μm or more and 5 μm or less. By setting the thickness of the barrier coat layer to 0.01 μm or more, the oxygen barrier property and water vapor barrier property of the laminate can be further improved. Furthermore, by setting the thickness of the barrier coat layer to 10 μm or less, the recyclability of the laminate can be maintained.

[0070] The barrier coat layer can be formed by dissolving or dispersing the above-mentioned material in water or a suitable solvent, applying the solution, and drying the solution. Alternatively, the barrier coat layer can be formed by applying a commercially available barrier coat agent and drying the solution.

[0071] In another embodiment, the barrier coat layer is a gas barrier coating film containing at least one resin composition such as a hydrolysate of a metal alkoxide or a hydrolyzed condensate of a metal alkoxide obtained by polycondensing a mixture of a metal alkoxide and a water-soluble polymer by a sol-gel method in the presence of a sol-gel catalyst, water, an organic solvent, etc. When the substrate has a vapor-deposited film made of an inorganic oxide, the barrier coat layer of this type is provided adjacent to the vapor-deposited film, thereby making it possible to effectively prevent cracks from occurring in the vapor-deposited film.

[0072] In one embodiment, the metal alkoxide is represented by the following general formula: R1 n M(OR 2 ) m (In the formula, R 1 , R 2 each represents an organic group having 1 to 8 carbon atoms, M represents a metal atom, n represents an integer of 0 or more, m represents an integer of 1 or more, and n+m represents the atomic valence of M.

[0073] As the metal atom M, for example, silicon, zirconium, titanium, aluminum, etc. can be used. Also, R 1 and R 2 Examples of the organic group represented by the formula (I) include alkyl groups such as a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, and an i-butyl group.

[0074] Examples of metal alkoxides that satisfy the above general formula include tetramethoxysilane (Si(OCH 3 ) 4 ), tetraethoxysilane (mass%) Si(OC 2 H 5 ) 4 ), tetrapropoxysilane (Si(OC 3 H 7 ) 4 ), tetrabutoxysilane (Si(OC 4 H 9 ) 4 ) etc.

[0075] It is also preferable to use a silane coupling agent together with the metal alkoxide. As the silane coupling agent, known organic reactive group-containing organoalkoxysilanes can be used, and in particular, organoalkoxysilanes having epoxy groups are preferred. As organoalkoxysilanes having epoxy groups, for example, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane can be mentioned.

[0076] Two or more of the above silane coupling agents may be used, and the silane coupling agent is preferably used in an amount within the range of about 1 to 20 parts by mass per 100 parts by mass of the total amount of the alkoxide.

[0077] As the water-soluble polymer, polyvinyl alcohol and an ethylene-vinyl alcohol copolymer are preferred, and from the viewpoints of oxygen barrier properties, water vapor barrier properties, water resistance and weather resistance, it is preferred to use these in combination.

[0078] The content of the water-soluble polymer in the gas barrier coating film is preferably 5 parts by mass or more and 500 parts by mass or less per 100 parts by mass of the metal alkoxide. By making the content of the water-soluble polymer in the gas barrier coating film 5 parts by mass or more per 100 parts by mass of the metal alkoxide, the oxygen barrier property and water vapor barrier property of the laminate can be further improved. Also, by making the content of the water-soluble polymer in the gas barrier coating film 500 parts by mass or less per 100 parts by mass of the metal alkoxide, the film formability of the gas barrier coating film can be improved.

[0079] The thickness of the gas barrier coating film is preferably from 0.01 μm to 100 μm, and more preferably from 0.1 μm to 50 μm, which can improve the oxygen barrier property and water vapor barrier property while maintaining recyclability. By making the thickness of the gas barrier coating film 0.01 μm or more, the oxygen barrier property and water vapor barrier property of the laminate can be improved. In addition, when the gas barrier coating film is provided adjacent to a vapor deposition film made of an inorganic oxide, the occurrence of cracks in the vapor deposition film can be prevented.

[0080] The gas barrier coating film can be formed by applying a composition containing the above-mentioned materials by a conventionally known means such as roll coating using a gravure roll coater or the like, spray coating, spin coating, dipping, brushing, bar coding, or an applicator, and then polycondensing the composition by a sol-gel method. As the sol-gel catalyst, an acid or an amine compound is preferable. As the amine compound, a tertiary amine that is substantially insoluble in water and soluble in an organic solvent is preferable, and examples thereof include N,N-dimethylbenzylamine, tripropylamine, tributylamine, and tripentylamine. Among these, N,N-dimethylbenzylamine is preferable. The sol-gel catalyst is preferably used in the range of 0.01 to 1.0 part by mass, and more preferably 0.03 to 0.3 part by mass, per 100 parts by mass of the metal alkoxide. By using the sol-gel catalyst in an amount of 0.01 part by mass or more per 100 parts by mass of the metal alkoxide, the catalytic effect can be improved. Furthermore, by setting the amount of the sol-gel catalyst to 1.0 part by mass or less per 100 parts by mass of the metal alkoxide, the thickness of the formed gas barrier coating film can be made uniform.

[0081] The composition may further contain an acid, which is used as a catalyst in the sol-gel process, mainly for the hydrolysis of alkoxides, silane coupling agents, and the like. The acid may be a mineral acid such as sulfuric acid, hydrochloric acid, or nitric acid, or an organic acid such as acetic acid, tartaric acid, etc. The amount of the acid used is preferably 0.001 mol or more and 0.05 mol or less based on the total molar amount of the alkoxide and the alkoxide portion (e.g., silicate portion) of the silane coupling agent. By using an acid in an amount of 0.001 mole or more based on the total mole amount of the alkoxide and the alkoxide portion (for example, silicate portion) of the silane coupling agent, the catalytic effect can be improved. Furthermore, by making the amount of the alkoxide and the alkoxide portion (for example, silicate portion) of the silane coupling agent 0.05 mol or less based on the total molar amount, the thickness of the gas barrier coating film formed can be made uniform.

[0082] The composition preferably contains water in an amount of 0.1 mol or more and 100 mol or less, more preferably 0.8 mol or more and 2 mol or less, per mol of the total molar amount of the alkoxides. By adjusting the water content to 0.1 mole or more per mole of the total molar amount of the alkoxides, the oxygen barrier property and water vapor barrier property of the laminate of the present invention can be improved. Furthermore, by adjusting the content of water to 100 moles or more per mole of the total molar amount of the alkoxides, the hydrolysis reaction can be carried out quickly.

[0083] The composition may also contain an organic solvent, such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, or n-butanol.

[0084] Hereinafter, one embodiment of the method for forming a gas barrier coating film will be described. First, a composition is prepared by mixing a metal alkoxide, a water-soluble polymer, a sol-gel catalyst, water, an organic solvent, and optionally a silane coupling agent, etc. In the composition, a polycondensation reaction gradually proceeds. Next, the composition is applied onto a substrate by the above-mentioned conventionally known method and dried. This drying process further advances the polycondensation reaction between the alkoxide and the water-soluble polymer (and the silane coupling agent, if the composition contains a silane coupling agent) to form a composite polymer layer. Finally, the composition is heated at a temperature of 20 to 250° C., preferably 50 to 220° C., for 1 second to 10 minutes to form a gas barrier coating film.

[0085] The barrier coat layer may have a printed layer formed thereon. The method for forming the printed layer is as described above.

[0086] (Gas barrier layer) The gas barrier layer in the laminate of the present invention contains a gas barrier resin, which can improve the oxygen barrier property and water vapor barrier property of the laminate. The gas barrier layer may have a single-layer structure or a multi-layer structure. When the gas barrier layer has a multi-layer structure, it is sufficient that at least one layer contains a gas barrier resin. In one embodiment, the multi-layered gas barrier layer is composed of a first polyethylene resin layer 13A, a first adhesive layer 13B, a layer 13C containing a gas barrier resin, a second adhesive layer 13D, and a second polyethylene resin layer 13E, as shown in FIG. 1. The adhesive layer will be described later.

[0087] Examples of gas barrier resins include ethylene-vinyl alcohol copolymers (EVOH), polyvinyl alcohol, polyacrylonitrile, polyamides such as nylon 6, nylon 6,6 and polymetaxylylene adipamide (MXD6), polyesters, polyurethanes, and (meth)acrylic resins.

[0088] The gas barrier layer preferably contains a compatibilizer. By containing the gas barrier layer, when the tube container produced using the laminate of the present invention is heated and melted for recycling, the gas barrier resin contained in the gas barrier layer and the polyethylene contained in the base material or the like are uniformly mixed together, which effectively prevents the physical properties from being deteriorated. In addition, the transparency is effectively prevented from being deteriorated. The compatibilizer may be appropriately selected from conventionally known ones and used. From the viewpoint of recyclability, however, unsaturated carboxylic acid modified polyolefins are preferred, and among them, maleic anhydride modified polyethylene is more preferred. When the gas barrier layer has a multi-layer structure, two or more layers may contain a compatibilizer.

[0089] The content of the compatibilizer in the entire gas barrier layer is preferably 5% by mass or more and 20% by mass or less. By adjusting the content of the compatibilizer in the entire gas barrier layer to 5% by mass or more, the above-mentioned deterioration in physical properties and deterioration in transparency can be more effectively prevented. By setting the content of the compatibilizer in the entire gas barrier layer to 20% by mass or less, the formability of the gas barrier layer can be improved. In addition, the laminate of the present invention can be recycled, and a decrease in strength of a film produced using the resulting resin can be prevented.

[0090] As long as the characteristics of the present invention are not impaired, the gas barrier layer may contain a resin other than the gas barrier resin, and examples of such resins include polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polyethylene naphthalate, (meth)acrylic resins, cellulose resins, vinyl resins, etc. Among these, polyethylene is preferred from the viewpoints of adhesion to the substrate and the like and recyclability of the laminate.

[0091] Furthermore, the gas barrier layer may contain the above-mentioned additives as long as the characteristics of the present invention are not impaired.

[0092] In one embodiment, the gas barrier layer is made of a film, which may be a stretched film or an unstretched film. From the viewpoint of the strength of the laminate, a stretched film is preferable. The stretched film may be a uniaxially stretched film or a biaxially stretched film.

[0093] In addition, the surface of the gas barrier layer is preferably subjected to the above-mentioned surface treatment, which can improve adhesion to adjacent layers.

[0094] When the gas barrier layer has a single-layer structure, the thickness thereof is preferably 10 μm or more and 30 μm or less, and more preferably 15 μm or more and 20 μm or less. By making the thickness of the gas barrier layer 10 μm or more, the gas barrier properties of the laminate of the present invention can be improved. Furthermore, by setting the thickness of the gas barrier layer to 30 μm or less, the recyclability of the laminate of the present invention can be improved.

[0095] When the gas barrier layer has a multi-layer structure, the sum of the thicknesses of the layers containing the gas barrier resin is preferably 20 μm or more and 100 μm or less, and more preferably 30 μm or more and 80 μm or less. By making the sum of the thicknesses of the layers containing the gas barrier resin 20 μm or more, the gas barrier properties of the laminate of the present invention can be improved. Furthermore, by making the sum of the thicknesses of the layers containing the gas barrier resin 100 μm or less, the recyclability of the laminate of the present invention can be improved.

[0096] In one embodiment, the gas barrier layer can be produced by forming a gas barrier resin into a film using a T-die method, an inflation method, or the like. The lamination with the substrate or the like can be carried out via a melt-extruded polyethylene layer or an adhesive layer, which will be described later.

[0097] (Melt-extruded polyethylene layer) In one embodiment, the laminate of the present invention may include a melt-extruded polyethylene layer between any layers, for example, between the surface resin layer and the substrate, between the substrate and the gas barrier layer, or between the gas barrier layer and the heat seal layer. The polyethylene contained in the melt-extruded polyethylene layer may be high density polyethylene, medium density polyethylene, low density polyethylene, linear low density polyethylene or very low density polyethylene. Among these, from the viewpoint of interlayer adhesion, low density polyethylene, linear low density polyethylene and very low density polyethylene are preferred.

[0098] The melt-extruded polyethylene layer may contain biomass-derived polyethylene, and the concentration of biomass-derived ethylene in the polyethylene contained in the melt-extruded polyethylene layer (hereinafter sometimes referred to as "biomass degree") is preferably 10% or more.

[0099] The melt extruded polyethylene layer may also include recycled polyethylene by mechanical recycling.

[0100] The melt-extruded polyethylene layer may contain the above-mentioned additives to the extent that the properties of the present invention are not impaired.

[0101] The thickness of the melt-extruded polyethylene layer is preferably 5 μm or more and 30 μm or less, and more preferably 10 μm or more and 20 μm or less. By making the thickness of the melt-extruded polyethylene layer 5 μm or more, the adhesion between the layers can be further improved. Furthermore, by making the thickness of the melt-extruded polyethylene layer 30 μm or less, the production cost of the laminate of the present invention can be reduced and the productivity can be improved.

[0102] The melt-extruded polyethylene layer can be formed by melt-extruding a resin composition containing at least polyethylene onto a substrate or the like.

[0103] (adhesive layer) In one embodiment, the laminate of the present invention may have an adhesive layer between any layers, for example, between the surface resin layer and the substrate, between the substrate and the gas barrier layer, or between the gas barrier layer and the heat seal layer. The laminate of the present invention may further include an adhesive layer as a layer constituting the gas barrier layer.

[0104] The adhesive layer may be formed from a conventionally known adhesive, which may be a one-component curing type, a two-component curing type, or a non-curing type. The adhesive may be either a solvent-free adhesive or a solvent-based adhesive, but from the standpoint of environmental impact, a solvent-free adhesive is preferably used. Examples of solvent-free adhesives include polyether adhesives, polyester adhesives, silicone adhesives, epoxy adhesives, and urethane adhesives, and among these, two-component curing urethane adhesives can be preferably used. Examples of solvent-based adhesives include rubber-based adhesives, vinyl-based adhesives, silicone-based adhesives, epoxy-based adhesives, phenol-based adhesives, and olefin-based adhesives.

[0105] Furthermore, when the adhesive layer is provided adjacent to the aluminum vapor-deposited film, more specifically, when the substrate has an aluminum vapor-deposited film and the adhesive layer is provided between the aluminum vapor-deposited film and the gas barrier layer, the adhesive layer preferably consists of a cured product of a resin composition containing a polyester polyol and an isocyanate compound. When molding a laminate including a vapor-deposited film, a bending load is applied to the laminate by a molding machine or the like, which may cause cracks in the aluminum vapor-deposited film. By configuring the adhesive layer as described above, it is possible to prevent cracks from occurring in the aluminum vapor-deposited film, and even if cracks do occur, it is possible to suppress a decrease in the oxygen barrier property and water vapor barrier property (flexural load resistance).

[0106] The polyester polyol has two or more hydroxyl groups as functional groups in one molecule. The isocyanate compound has two or more isocyanate groups as functional groups in one molecule. The polyester polyol has, for example, a polyester structure or a polyester polyurethane structure as a main skeleton.

[0107] As a specific example of a resin composition (adhesive) containing a polyester polyol and an isocyanate compound, the PASLIM series sold by DIC Corporation can be used.

[0108] The resin composition may further contain a phosphoric acid-modified compound, a plate-like inorganic compound, a coupling agent, cyclodextrin and / or a derivative thereof, and the like.

[0109] As the polyester polyol having two or more hydroxyl groups in one molecule as a functional group, for example, the following [First Example] to [Third Example] can be used. [Example 1] Polyester polyol obtained by polycondensation of ortho-oriented polycarboxylic acid or its anhydride with polyhydric alcohol [Example 2] Polyester polyol with glycerol structure [Example 3] Polyester polyol with isocyanuric ring Each polyester polyol will be described below.

[0110] The polyester polyol according to the first example is a polycondensate obtained by polycondensing a polycarboxylic acid component containing at least one or more types of orthophthalic acid and its anhydride, and a polyhydric alcohol component containing at least one type selected from the group consisting of ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, and cyclohexanedimethanol. In particular, polyester polyols in which the content of orthophthalic acid or its anhydride in the total polyvalent carboxylic acid components is 70 to 100 mass % are preferred.

[0111] The polyester polyol according to the first example essentially contains orthophthalic acid and its anhydride as the polycarboxylic acid component, but may be copolymerized with other polycarboxylic acid components as long as the effect of the present embodiment is not impaired. Specifically, the polybasic acids include aliphatic polybasic carboxylic acids such as succinic acid, adipic acid, azelaic acid, sebacic acid, and dodecane dicarboxylic acid, unsaturated bond-containing polybasic carboxylic acids such as maleic anhydride, maleic acid, and fumaric acid, alicyclic polybasic carboxylic acids such as 1,3-cyclopentane dicarboxylic acid and 1,4-cyclohexane dicarboxylic acid, aromatic polybasic carboxylic acids such as terephthalic acid, isophthalic acid, pyromellitic acid, trimellitic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, naphthalic acid, biphenyl dicarboxylic acid, 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid, anhydrides of these dicarboxylic acids, and ester-forming derivatives of these dicarboxylic acids, p-hydroxybenzoic acid, p-(2-hydroxyethoxy)benzoic acid, and ester-forming derivatives of these dihydroxycarboxylic acids. Among these, succinic acid, 1,3-cyclopentane dicarboxylic acid, and isophthalic acid are preferred. Two or more of the above other polyvalent carboxylic acids may be used.

[0112] As a polyester polyol according to a second example, a polyester polyol having a glycerol skeleton represented by general formula (1) can be mentioned. [ka] In the general formula (1), R 1 , R 2 , R 3 are each independently H (hydrogen atom) or a group represented by the following general formula (2). [ka]

[0113] In formula (2), n represents an integer of 1 to 5, X represents an arylene group selected from the group consisting of 1,2-phenylene groups, 1,2-naphthylene groups, 2,3-naphthylene groups, 2,3-anthraquinonediyl groups, and 2,3-anthracenediyl groups, which may have a substituent, and Y represents an alkylene group having 2 to 6 carbon atoms. However, R 1 , R 2 , R 3 At least one of the groups represented by general formula (2) is represented by the formula (2).

[0114] In the general formula (1), R 1 , R 2 , R 3 At least one of R must be a group represented by general formula (2). 1 , R 2 , R 3 It is preferable that all of them are groups represented by formula (2).

[0115] Also, R 1 , R 2 , R 3 is a group represented by general formula (2), and R 1 , R 2 , R 3 and a compound in which any two of R 1 , R 2 , R 3 may be a mixture of two or more compounds in which all of the above are groups represented by general formula (2).

[0116] X represents an optionally substituted arylene group selected from the group consisting of a 1,2-phenylene group, a 1,2-naphthylene group, a 2,3-naphthylene group, a 2,3-anthraquinonediyl group, and a 2,3-anthracenediyl group. When X is substituted, it may be substituted with one or more substituents, and the substituent is attached to any carbon atom on X other than the free radical. The substituents include a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, a N-ethylcarbamoyl group, a phenyl group, and a naphthyl group.

[0117] In the general formula (2), Y represents an alkylene group having 2 to 6 carbon atoms, such as an ethylene group, a propylene group, a butylene group, a neopentylene group, a 1,5-pentylene group, a 3-methyl-1,5-pentylene group, a 1,6-hexylene group, a methylpentylene group, or a dimethylbutylene group. Among these, Y is preferably a propylene group or an ethylene group, and most preferably an ethylene group.

[0118] The polyester resin compound having a glycerol skeleton represented by general formula (1) can be synthesized by reacting glycerol, an aromatic polycarboxylic acid or its anhydride in which a carboxylic acid is substituted at the ortho position, and a polyhydric alcohol component as essential components.

[0119] Examples of aromatic polycarboxylic acids or anhydrides in which a carboxylic acid is substituted at the ortho position include orthophthalic acid or anhydride, naphthalene 2,3-dicarboxylic acid or anhydride, naphthalene 1,2-dicarboxylic acid or anhydride, anthraquinone 2,3-dicarboxylic acid or anhydride, and 2,3-anthracene carboxylic acid or anhydride. These compounds may have a substituent at any carbon atom of the aromatic ring, such as a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, an N-ethylcarbamoyl group, a phenyl group, or a naphthyl group.

[0120] Examples of the polyhydric alcohol component include alkylene diols having 2 to 6 carbon atoms, such as ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methylpentanediol, and dimethylbutanediol.

[0121] The polyester polyol according to the third example is a polyester polyol having an isocyanuric ring represented by the following general formula (3). [ka] In the general formula (3), R 1 , R 2 , R 3 are each independently "-(CH 2 )n1-OH (wherein n1 represents an integer of 2 to 4)" or a structure represented by general formula (4). [ka]

[0122] In the general formula (4), n2 represents an integer of 2 to 4, n3 represents an integer of 1 to 5, X represents an arylene group selected from the group consisting of a 1,2-phenylene group, a 1,2-naphthylene group, a 2,3-naphthylene group, a 2,3-anthraquinonediyl group, and a 2,3-anthracenediyl group, which may have a substituent, and Y represents an alkylene group having 2 to 6 carbon atoms. 1 , R 2 , R 3 At least one of the above is a group represented by general formula (4).

[0123] In the general formula (3), -(CH 2 The alkylene group represented by n1- may be linear or branched. Among these, n1 is preferably 2 or 3, and most preferably 2.

[0124] In the general formula (4), n2 represents an integer of 2 to 4; n3 represents an integer of 1 to 5. X represents an optionally substituted arylene group selected from the group consisting of a 1,2-phenylene group, a 1,2-naphthylene group, a 2,3-naphthylene group, a 2,3-anthraquinonediyl group, and a 2,3-anthracenediyl group.

[0125] When X is substituted, it may be substituted with one or more substituents, and the substituent is attached to any carbon atom on X other than the free radical. The substituents include a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, a N-ethylcarbamoyl group, a phenyl group, and a naphthyl group. The substituent for X is preferably a hydroxyl group, a cyano group, a nitro group, an amino group, a phthalimido group, a carbamoyl group, an N-ethylcarbamoyl group, or a phenyl group, and most preferably a hydroxyl group, a phenoxy group, a cyano group, a nitro group, a phthalimido group, or a phenyl group.

[0126] In the general formula (4), Y represents an alkylene group having 2 to 6 carbon atoms, such as an ethylene group, a propylene group, a butylene group, a neopentylene group, a 1,5-pentylene group, a 3-methyl-1,5-pentylene group, a 1,6-hexylene group, a methylpentylene group, or a dimethylbutylene group. Among these, Y is preferably a propylene group or an ethylene group, and most preferably an ethylene group.

[0127] In the general formula (3), R 1 , R 2 , R 3 At least one of R is a group represented by general formula (4). 1 , R 2 , R 3 It is preferable that all of them are groups represented by formula (4).

[0128] Also, R 1, R 2 , R 3 is a group represented by general formula (4), and R 1 , R 2 , R 3 and a compound in which any two of R 1 , R 2 , R 3 may be a mixture of two or more compounds in which all of the above are groups represented by general formula (4).

[0129] The polyester polyol having an isocyanuric ring represented by the general formula (3) can be synthesized by reacting a triol having an isocyanuric ring, an aromatic polycarboxylic acid or its anhydride in which a carboxylic acid is substituted at the ortho position, and a polyhydric alcohol component as essential components.

[0130] Examples of triols having an isocyanuric ring include alkylene oxide adducts of isocyanuric acid such as 1,3,5-tris(2-hydroxyethyl)isocyanuric acid and 1,3,5-tris(2-hydroxypropyl)isocyanuric acid.

[0131] Examples of aromatic polycarboxylic acids or anhydrides in which a carboxylic acid is substituted at the ortho position include orthophthalic acid or anhydride, naphthalene 2,3-dicarboxylic acid or anhydride, naphthalene 1,2-dicarboxylic acid or anhydride, anthraquinone 2,3-dicarboxylic acid or anhydride, and 2,3-anthracene carboxylic acid or anhydride, etc. These compounds may have a substituent on any carbon atom of the aromatic ring.

[0132] Examples of the substituent include a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, an N-ethylcarbamoyl group, a phenyl group, and a naphthyl group.

[0133] The polyhydric alcohol component may be an alkylene diol having 2 to 6 carbon atoms, such as ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methylpentanediol, or dimethylbutanediol. Among these, polyester polyol compounds having an isocyanuric ring, which use 1,3,5-tris(2-hydroxyethyl)isocyanuric acid or 1,3,5-tris(2-hydroxypropyl)isocyanuric acid as a triol compound having an isocyanuric ring, orthophthalic anhydride as an aromatic polycarboxylic acid or its anhydride in which a carboxylic acid is substituted at the ortho position, and ethylene glycol as a polyhydric alcohol, are particularly excellent in oxygen barrier properties and adhesion and are therefore preferred.

[0134] The isocyanuric ring is highly polar and trifunctional, and can increase the polarity of the entire system and increase the crosslink density. From this viewpoint, it is preferable that the adhesive resin contains 5% by mass or more of the isocyanuric ring based on the total solid content of the adhesive resin.

[0135] The isocyanate compound has two or more isocyanate groups in the molecule. The isocyanate compound may be either aromatic or aliphatic, and may be either a low molecular weight compound or a high molecular weight compound. Furthermore, the isocyanate compound may be a blocked isocyanate compound obtained by subjecting a known isocyanate blocking agent to an addition reaction by a known, conventional appropriate method. Among these, from the viewpoints of adhesiveness and retort resistance, polyisocyanate compounds having three or more isocyanate groups are preferred, and from the viewpoints of oxygen barrier property and water vapor barrier property, aromatic compounds are preferred.

[0136] Specific examples of the isocyanate compound include tetramethylene diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, metaxylylene diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, and trimers of these isocyanate compounds, as well as adducts, biurets, and allophanates obtained by reacting these isocyanate compounds with low-molecular-weight active hydrogen compounds or their alkylene oxide adducts, or high-molecular-weight active hydrogen compounds. Examples of low molecular weight active hydrogen compounds include ethylene glycol, propylene glycol, metaxylylene alcohol, 1,3-bishydroxyethylbenzene, 1,4-bishydroxyethylbenzene, trimethylolpropane, glycerol, pentaerythritol, erythritol, sorbitol, ethylenediamine, monoethanolamine, diethanolamine, triethanolamine, and metaxylylenediamine. Examples of molecular weight active hydrogen compounds include polymeric active hydrogen compounds such as various polyester resins, polyether polyols, and polyamides.

[0137] In one embodiment, the resin composition contains a phosphoric acid-modified compound, and for example, a compound represented by the following general formula (5) or (6) can be used. [ka] In the general formula (5), R 1 , R 2 , R 3 is a group selected from a hydrogen atom, an alkyl group having 1 to 30 carbon atoms, a (meth)acryloyl group, a phenyl group which may have a substituent, and an alkyl group having 1 to 4 carbon atoms which has a (meth)acryloyloxy group, at least one of which is a hydrogen atom, and n is an integer of 1 to 4. [ka] In the formula, R 4 , R5 represents a group selected from a hydrogen atom, an alkyl group having 1 to 30 carbon atoms, a (meth)acryloyl group, a phenyl group which may have a substituent, and an alkyl group having 1 to 4 carbon atoms which has a (meth)acryloyloxy group; n represents an integer of 1 to 4, x represents an integer of 0 to 30, and y represents an integer of 0 to 30, except for the case where both x and y are 0.

[0138] More specific examples include phosphoric acid, pyrophosphoric acid, triphosphoric acid, methyl acid phosphate, ethyl acid phosphate, butyl acid phosphate, dibutyl phosphate, 2-ethylhexyl acid phosphate, bis(2-ethylhexyl) phosphate, isododecyl acid phosphate, butoxyethyl acid phosphate, oleyl acid phosphate, tetracosyl acid phosphate, 2-hydroxyethyl methacrylate acid phosphate, and polyoxyethylene alkyl ether phosphate, and one or more of these can be used.

[0139] The content of the phosphoric acid-modified compound in the resin composition is preferably from 0.005% by mass to 10% by mass, and more preferably from 0.01% by mass to 1% by mass. By adjusting the content of the phosphoric acid-modified compound to 0.005% by mass or more, the oxygen barrier property and water vapor barrier property of the laminate of the present invention can be improved. Furthermore, by setting the content of the phosphoric acid-modified compound to 10% by mass or less, the adhesiveness of the adhesive layer can be improved.

[0140] The resin composition containing the polyester polyol, the isocyanate compound and the phosphoric acid-modified compound may contain a plate-like inorganic compound, which can improve the adhesiveness of the adhesive layer and the bending load resistance of the laminate of the present invention. Examples of the plate-like inorganic compounds include kaolinite-serpentine group clay minerals (such as halloysite, kaolinite, endelite, dickite, nacrite, antigorite, and chrysotile) and pyrophyllite-talc group (such as pyrophyllite, talc, and keroli).

[0141] Examples of the coupling agent include silane-based coupling agents, titanium-based coupling agents, and aluminum-based coupling agents represented by the following general formula (7). These coupling agents may be used alone or in combination of two or more kinds. [ka]

[0142] Examples of silane coupling agents include vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-methacryloxytrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, γ-methacryloxypropyltriethoxysilane, N-β( aminoethyl) γ-aminopropyl methyl dimethoxysilane, N-β (aminoethyl) γ-aminopropyl trimethoxysilane, N-β (aminoethyl) γ-aminopropyl triethoxysilane, γ-aminopropyl trimethoxysilane, γ-aminopropyl triethoxysilane, N-phenyl-γ-aminopropyl trimethoxysilane, γ-chloropropyl trimethoxysilane, γ-mercaptopropyl trimethoxysilane, 3-isocyanatopropyl triethoxysilane, 3-acryloxypropyl trimethoxysilane and 3-triethoxysilyl-N-(1,3-dimethyl-butylidene).

[0143] Examples of titanium-based coupling agents include isopropyl triisostearoyl titanate, isopropyl tri(N-aminoethyl-aminoethyl) titanate, isopropyl tridodecylbenzenesulfonyl titanate, isopropyl tris(dioctyl pyrophosphate) titanate, tetraoctyl bis(didodecyl phosphite) titanate, tetraoctyl bis(ditridecyl phosphite) titanate, bis(dioctyl pyrophosphate)oxyacetate titanate, bis(dioctyl pyrophosphate)ethylene titanate, isopropyl trioctyl nor titanate, isopropyl dimethacryl isostearoyl titanate, isopropyl isostearoyl diacryl titanate, diisostearoyl ethylene titanate, isopropyl tri(dioctyl phosphate) titanate, isopropyl tricumyl phenyl titanate, and dicumyl phenyl oxyacetate titanate.

[0144] Specific examples of aluminum-based coupling agents include acetoalkoxyaluminum diisopropylate, diisopropoxyaluminum ethyl acetoacetate, diisopropoxyaluminum monomethacrylate, isopropoxyaluminum alkyl acetoacetate mono(dioctyl phosphate), aluminum 2-ethylhexanoate oxide trimer, aluminum stearate oxide trimer, and alkyl acetoacetate aluminum oxide trimer.

[0145] The resin composition may contain cyclodextrin and / or a derivative thereof, which can improve the adhesiveness of the adhesive layer and can further improve the bending load resistance of the laminate of the present invention. Specifically, for example, cyclodextrin, alkylated cyclodextrin, acetylated cyclodextrin, hydroxyalkylated cyclodextrin, and other cyclodextrins in which the hydrogen atom of the hydroxyl group of the glucose unit of cyclodextrin is substituted with another functional group can be used. Branched cyclic dextrins can also be used. Furthermore, the cyclodextrin skeleton in cyclodextrin and cyclodextrin derivatives may be any of α-cyclodextrin consisting of six glucose units, β-cyclodextrin consisting of seven glucose units, and γ-cyclodextrin consisting of eight glucose units. These compounds may be used alone or in combination of two or more. Hereinafter, these cyclodextrins and / or their derivatives may be collectively referred to as dextrin compounds.

[0146] From the viewpoint of compatibility and dispersibility in the resin composition, it is preferable to use a cyclodextrin derivative as the cyclodextrin compound.

[0147] Examples of alkylated cyclodextrins include methyl-α-cyclodextrin, methyl-β-cyclodextrin, and methyl-γ-cyclodextrin. These compounds may be used alone or in combination of two or more.

[0148] Examples of acetylated cyclodextrin include monoacetyl-α-cyclodextrin, monoacetyl-β-cyclodextrin, and monoacetyl-γ-cyclodextrin. These compounds may be used alone or in combination of two or more.

[0149] Examples of hydroxyalkylated cyclodextrins include hydroxypropyl-α-cyclodextrin, hydroxypropyl-β-cyclodextrin, and hydroxypropyl-γ-cyclodextrin, etc. These compounds may be used alone or in combination of two or more kinds.

[0150] As long as the properties of the present invention are not impaired, the adhesive layer may contain additives such as pigments such as titanium oxide, zinc oxide and carbon black, dyes such as disperse dyes, acid dyes and cationic dyes, antioxidants, lubricants, colorants, stabilizers, wetting agents, thickeners, coagulants, gelling agents, anti-settling agents, softeners, hardeners, plasticizers, leveling agents, ultraviolet absorbers and flame retardants.

[0151] The thickness of the adhesive layer is not particularly limited, and can be, for example, 1 μm or more and 5 μm or less.

[0152] (Tube container body) The tube container body of the present invention is characterized by comprising the above-mentioned laminate. The tube container body of the present invention will be described below with reference to the drawings. Fig. 2 is a diagram showing a simplified configuration of a tube container 20, and Fig. 3 is a cross-sectional view taken along line AA in Fig. 2. As shown in Fig. 2, the tube container body 21 is characterized by having a head 22 and a body 23, and the body 23 being formed from the laminate.

[0153] (head) The head portion 22 has a shoulder portion 24 connected to one end of the body portion 23 and a sampling port portion 25 connected to the shoulder portion 24. In one embodiment, the spout portion 25 includes a thread 27 for screwing the cap 26 thereon.

[0154] In one embodiment, the head portion is made of a resin composition containing polyethylene, which can improve the recyclability of the tube container. As the polyethylene, high density polyethylene, medium density polyethylene, low density polyethylene, linear low density polyethylene, and very low density polyethylene can be used. Among these, high density polyethylene is preferred from the viewpoint of shape retention.

[0155] The resin composition may contain polyethylene derived from biomass or polyethylene recycled by calcinal recycling.

[0156] The resin composition may contain the above-mentioned additives as long as the characteristics of the present invention are not impaired.

[0157] The method for producing the head is not particularly limited, and the head can be produced by a conventionally known method. For example, the head can be produced by a compression molding method or an injection molding method, and can be joined to the body.

[0158] When a tube container is manufactured using a compression molding method, a body portion is attached to a male mold having a convex portion on the top, the male mold and female mold are then placed opposite each other, a molten resin composition is supplied into the male and female molds, and the head portion is formed by compression molding and joined to one opening of the body portion, thereby manufacturing a tube container consisting of a head and a body portion. Furthermore, when a tube container is manufactured using an injection molding method, the body portion is attached to a male mold having a convex portion on the top, the male mold and the female mold are opposed to each other, a molten resin composition is supplied from a gate, and the head portion is formed by injection molding and joined to one opening of the body portion, thereby manufacturing a tube container consisting of a head and a body portion.

[0159] (Torso) In the tube container body 21 of the present invention, the body portion 23 is connected to the shoulder portion 24 of the head portion 22 . The body portion 23 is formed by rolling the laminate into a cylindrical shape, overlapping the surface resin layer and the heat seal layer, and heat sealing the overlapped portion to provide a welded portion 28. The body 23 also includes a bottom seal 29 formed by heat sealing the opening of the rolled laminate.

[0160] Heat sealing can be performed by a conventional method such as bar sealing, rotary roll sealing, belt sealing, impulse sealing, high frequency sealing, ultrasonic sealing, or flame sealing.

[0161] (Tube container) The tube container of the present invention comprises the above-mentioned tube container body and a cap. In one embodiment, the tube 20 also includes a cap 26 that fits over the head 22 .

[0162] (cap) The cap is removably attached to the extraction port of the head and serves to close the extraction port. The cap is made of a resin composition including a thermoplastic resin. Examples of the thermoplastic resin include polyolefins such as polyethylene and polypropylene, polyesters, cellulose resins, and vinyl resins, and from the viewpoint of recyclability, polyethylene is particularly preferred. As the polyethylene, high-density polyethylene, medium-density polyethylene, low-density polyethylene, linear low-density polyethylene, and very low-density polyethylene can be used. Among these, high density polyethylene is preferred from the viewpoints of shape retention and ease of opening. Biomass-derived polyethylene and mechanically recycled polyethylene can also be used. Furthermore, the resin composition may contain the above-mentioned additives as long as the characteristics of the present invention are not impaired.

[0163] The cap may be of a screw type having a groove on the inner surface thereof so as to screw into the threaded thread 27 of the extraction port 25, as shown in FIG. 2, or it may be of a plug type which is fitted to the extraction port 27 by plugging it. EXAMPLES

[0164] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0165] Example 1 (Preparation of Laminate) Linear low-density polyethylene 1 (ExxonMobil, Exceed2018HA, density 0.918g / cm 3) and high-density polyethylene (ExxonMobil, HTA108, density 0.961g / cm 3 ) and linear low-density polyethylene 2 (Dow Chemical, Dowlex 2098G, density 0.926 g / cm 3 ) were co-extruded by an inflation method to obtain a substrate film. The substrate film obtained as described above had a three-layer structure with a total thickness of 40 μm, comprising a 10 μm-thick layer composed of linear low-density polyethylene 1, a 20 μm-thick layer composed of high-density polyethylene, and a 10 μm-thick layer composed of linear low-density polyethylene 2 (linear low-density polyethylene layer / high-density polyethylene layer / linear low-density polyethylene layer). An aluminum vapor deposition film having a thickness of 20 nm was formed by PVD on the surface of the layer composed of the linear low-density polyethylene 1 of the substrate film to obtain a substrate.

[0166] A urethane adhesive (RU004 / H1, manufactured by Rock Paint) was applied to the vapor deposition surface of the substrate and dried to form a 3 μm thick adhesive layer, and a 100 μm thick unstretched linear low-density polyethylene film (manufactured by Tamapoly, product name: UB-3) was laminated on top of this adhesive layer as a surface resin layer.

[0167] Linear low-density polyethylene (Dow Chemical, Dowlex 2045G, density 0.920 g / cm 3 ), adhesive resin (Mitsui Chemicals, Admer NF557), ethylene-vinyl alcohol copolymer (Kuraray, Eval H171B, density 1.17 g / cm3, ethylene content 38 mol%), adhesive resin (Mitsui Chemicals, Admer NF557), linear low-density polyethylene (Dow Chemical, Dowlex 2045G, density 0.920 g / cm 3 ) were co-extruded by the inflation method to form a five-layer gas barrier layer. The gas barrier layer obtained as described above had a five-layer structure with a total thickness of 60 μm, including a 17.5 μm thick layer composed of linear low-density polyethylene, a 5 μm thick layer composed of adhesive resin, a 15 μm thick layer composed of ethylene-vinyl alcohol copolymer, a 5 μm thick layer composed of adhesive resin, and a 17.5 μm thick layer composed of linear low-density polyethylene (linear low-density polyethylene layer / adhesive resin layer / ethylene-vinyl alcohol copolymer layer / adhesive resin layer / linear low-density polyethylene layer).

[0168] A low-density polyethylene film (Novatec LC600A, made by Nippon Polyethylene Co., Ltd., density 0.918 g / cm3) was applied to the non-evaporated film of the substrate. 3 ) was melt-extruded to form a melt-extruded polyethylene layer having a thickness of 20 μm, and a layer composed of one of the linear low density polyethylenes provided in the gas barrier layer was laminated via this melt-extruded polyethylene layer.

[0169] On the other layer made of linear low-density polyethylene that is provided in the gas barrier layer, a low-density polyethylene (Nippon Polyethylene, Novatec LC600A, density 0.918 g / cm 3 ) was melt-extruded to form a melt-extruded polyethylene layer having a thickness of 20 μm, and a 100 μm-thick unstretched linear low-density polyethylene film (manufactured by Tamapoly Co., Ltd., product name: UB-3) was laminated as a heat seal layer through this melt-extruded polyethylene layer to produce a laminate of the present invention. The polyethylene content in this laminate was 92%.

[0170] Example 2 Linear low-density polyethylene (Dow Chemical, Dowlex 2045G, density 0.920 g / cm 3 ) and a compatibilizer (Dow Chemical, maleic anhydride modified polyethylene, Retain 3000, density 0.870 g / cm 3 ) were blended in a ratio of linear low-density polyethylene:compatibilizer=93% by mass:7% by mass to prepare a blend resin.

[0171] The blend resin prepared above, an adhesive resin (Mitsui Chemicals, Admer NF557), an ethylene-vinyl alcohol copolymer (Kuraray, EVAL H171B, density 1.17 g / cm3, ethylene content 38 mol%), an adhesive resin (Mitsui Chemicals, Admer NF557), and the blend resin were co-extruded into a five-layer film by the inflation method to obtain a gas barrier layer. The gas barrier layer obtained as described above had a five-layer structure with a total thickness of 60 μm, including a layer composed of the blend resin having a thickness of 17.5 μm, a layer composed of the adhesive resin having a thickness of 5 μm, a layer composed of the ethylene-vinyl alcohol copolymer having a thickness of 15 μm, a layer composed of the adhesive resin having a thickness of 5 μm, and a layer composed of the blend resin having a thickness of 17.5 μm (blend resin layer / adhesive resin layer / ethylene-vinyl alcohol copolymer layer / adhesive resin layer / blend resin layer).

[0172] A laminate of the present invention was produced in the same manner as in Example 1, except that the gas barrier layer was changed to one produced as described above. The polyethylene content in this laminate was 91%.

[0173] Comparative Example 1 A laminate was produced in the same manner as in Example 1, except that the base film was a biaxially oriented polyethylene terephthalate film having a thickness of 12 μm (Ester film E5100, manufactured by Toyobo Co., Ltd.). The polyethylene content in this laminate was 87%.

[0174] (Preparation of tube containers) The laminate obtained as described above was cut into a 120 mm wide slit using a bobbin cutter, and both ends in the width direction were overlapped so that the overlap width was about 1.5 mm, and then the overlapped ends were heat-sealed to obtain a cylindrical raw roll with a tube. The obtained raw roll was cut in the length direction to 122 mm to produce a cylindrical body portion that would become the body portion of the tube container.

[0175] The cylindrical body was attached to a mandrel for forming a tube container, and a head portion consisting of a truncated cone-shaped shoulder portion and a cylindrical extraction port portion connected to the shoulder portion was attached to one end of the cylindrical body using high-density polyethylene (Novatec HJ360, made by Nippon Polyethylene Co., Ltd., density 0.951 g / cm 3 ) was molded by injection molding to produce a tube container as shown in Figure 3. The spout part at the top of the obtained tube container body had an outer diameter of 13 mm, a height of 1.5 mm, and a thread was provided on the side of the spout part. The outer diameter of the shoulder part was 38 mm.

[0176] Next, the high density polyethylene was injected into a die for forming a cap and molded to prepare a cap, thereby obtaining a tube container of the present invention.

[0177] <<Recyclability evaluation>> The recyclability of the laminates for packaging materials obtained in the above Examples and Comparative Examples was evaluated based on the following evaluation criteria. The evaluation results are summarized in Table 1. (Evaluation Criteria) ◯: The content of the same polyolefin in the laminate for packaging material was 90% by mass or more. ×: The content of the same polyolefin in the laminate for packaging material was less than 90 mass %.

[0178] <<Shoulder adhesive strength>> Test pieces were obtained by cutting a strip 15 mm wide from the joining point between the body and shoulder toward the bottom hem. The test piece was pulled at a test speed of 300 mm / min using a tensile tester (Orientec Co., Ltd., RTC-1310A) to measure the peel strength when the body part was peeled off from the shoulder part. The measurement results are summarized in Table 1.

[0179] <<Side seam strength>> The specimen was cut into strips 15 mm wide perpendicular to the side seam (overlapping area) of the body, and pulled at a test speed of 300 mm / min using a tensile tester to measure the strength at break. The measurement results are summarized in Table 1.

[0180] <<Leakage evaluation>> A cap was screwed onto the extraction opening of the tube container body, and then 120 g of commercially available toothpaste was poured into the opening of the cylindrical body, which was then heat-sealed. The tightening torque set for capping was 4.7 kg cm. The container was left at room temperature for two weeks, and visually inspected every day to see if there was any leakage of the contents. The evaluation criteria for leakage were as follows: (Evaluation Criteria) 〇: No leakage of contents was observed even after 2 weeks. ×: Leakage of contents was observed within 2 weeks

[0181] [Table 1] [Explanation of symbols]

[0182] 10: laminate, 11: surface resin layer, 12: substrate, 13: gas barrier layer, 13A: first polyethylene resin layer, 13B: first adhesive layer, 13C: layer containing gas barrier resin, 13D: second adhesive layer, 13E: second polyethylene resin layer, 14: heat seal layer, 15: vapor deposition film, 20: tube container, 21: tube container body, 22: head, 23: body, 24: shoulder, 25: extraction port, 26: cap, 27: thread, 28: welded portion, 29: bottom seal portion

Claims

1. A surface resin layer, a substrate, a gas barrier layer, and a heat seal layer are provided in this order, the surface resin layer, the base material, and the heat seal layer are made of the same material, The substrate has a vapor-deposited film on at least one surface, The surface resin layer has heat sealability, the same material being polyethylene; the gas barrier layer comprises a first polyethylene resin layer, a first adhesive layer, a layer containing a gas barrier resin having a thickness of 20 μm or more and 100 μm or less, a second adhesive layer, and a second polyethylene resin layer; A laminate, characterized in that the content of polyethylene in the entire laminate is 90 mass% or more.

2. The laminate according to claim 1, further comprising a melt-extruded polyethylene layer or an adhesive layer at least one of between the surface resin layer and the substrate, between the substrate and the gas barrier layer, and between the gas barrier layer and the heat seal layer.

3. 3. The laminate according to claim 1, wherein the polyethylene constituting the surface resin layer and the heat seal layer is a low-density polyethylene and / or a linear low-density polyethylene.

4. The laminate according to any one of claims 1 to 3, wherein the vapor-deposited film is a metal vapor-deposited film.

5. The laminate according to any one of claims 1 to 4, wherein the surface resin layer and the heat seal layer have a thickness of 30 µm or more and 150 µm or less.

6. The laminate according to any one of claims 1 to 5, wherein the substrate has a thickness of 10 µm or more and 50 µm or less.

7. The laminate according to any one of claims 1 to 6, wherein the vapor-deposited film has a thickness of 1 nm or more and 150 nm or less.

8. The laminate according to any one of claims 1 to 7, which is used for a tube container.

9. The device has a head and a body, The head portion has a shoulder portion connected to one end of the body portion and a sampling port portion connected to the shoulder portion, A tube container, characterized in that the body portion is formed from the laminate according to any one of claims 1 to 8.

10. The tube container according to claim 9, wherein the head portion is made of a resin composition containing polyethylene.

11. The tube container according to claim 9 or 10, further comprising a cap made of a resin composition containing polyethylene.

Citation Information

Patent Citations

  • Laminated material for forming a flexible container, assembly comprising said laminated material and a tube head, and flexible container comprising said assembly and a cap

    EP3482928A1

  • Laminated tube container

    JP2002361776A

  • Laminate tube container

    JP2006282184A

  • Multi-layered film for laminate tube, and laminate tube using the multi-layered film

    JP2013220848A

  • Laminating material for laminate tube container and packaging container using the same

    JP2014091265A